2023
DOI: 10.1098/rspb.2023.1010
|View full text |Cite
|
Sign up to set email alerts
|

Doomed drones? Using passage experiments and mathematical modelling to determine Deformed wing virus population dynamics in male honeybees

Abstract: Varroa destructor is an ectoparasitic mite of honeybees which vectors a range of pathogenic viruses, the most notable being Deformed wing virus (DWV). Mites parasitise bees during pupal development and male honeybees, drones, have a longer development cycle than female workers (24 versus 21 days), allow for more progeny mites to develop per foundress (1.6–2.5 compared to 0.7–1.45). How this longer exposure time influences evolution of the transmitted virus population is unknown. Using uniquely tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Experimental injection of BQCV in honeybee pupae, mimicking varroa-mediated transmission, suggests that BQCV may be too virulent to develop an epidemically stable and successful virus-vector relationship with varroa at the colony and inter-colony levels [ 82 , 83 ]. Other factors, such as infection dose delivered by the mite, may be important to determine the nature of the association between the vector and the virus [ 84 ]. The apparent rise in prevalence and load of BQCV in presence of varroa mites might well be due to the suppressed immune response of bees as a consequence of varroa parasitism or infection by other viruses such as DWV [ 38 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental injection of BQCV in honeybee pupae, mimicking varroa-mediated transmission, suggests that BQCV may be too virulent to develop an epidemically stable and successful virus-vector relationship with varroa at the colony and inter-colony levels [ 82 , 83 ]. Other factors, such as infection dose delivered by the mite, may be important to determine the nature of the association between the vector and the virus [ 84 ]. The apparent rise in prevalence and load of BQCV in presence of varroa mites might well be due to the suppressed immune response of bees as a consequence of varroa parasitism or infection by other viruses such as DWV [ 38 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of any sex-link between this virus and any other insect including ants. With regard to honey bees, a recent study by [33] (and the references therein) reported that emerging drones exhibited overt developmental deformities similar to those seen in the worker brood when injected with DWV as white-eyed pupae. They also reported that a percentage of drones without any outward deformities carried very high titer levels equivalent to drones with outward deformities.…”
Section: Identification Of the Replication Form Of Dwv In S Invicta D...mentioning
confidence: 92%